Lathosterolosis: a rare cholesterol metabolism disorder with a wide range of clinical variability - Sobu, Elif; Ozcora, Gul Demet Kaya; Gorukmez, Ozlem; Sahinoglu, Bahtiyar (WALTER DE GRUYTER GMBH)
Objectives: Lathosterolosis is a rare autosomal recessive congenital disease that occurs due to homozygous or compound heterozygous mutations in the sterol C5-desaturase (SC5D) gene. We report a male patient with biallelic missense variant detected in the SC5D gene.Case presentation: An eight-month-old male patient was referred to the department of paediatric neurology for status epilepticus. He had no remarkable dysmorphic features except micrognathia, ptotic ear and thin-stranded hair. Laboratory tests revealed an alanine aminotransferase level of 502 IU/L and an aspartate aminotransferase level of 279 IU/L; other biochemical test results were normal. The brain MRI revealed atrophic changes in both hemispheres. A decrease in the volume of brain stem and thin corpus callosum were noticeable. Whole exome sequencing was performed because of consanguineous marriage and sibling death in his medical history, and the encountered features were consistent with suspected neurometabolic disease in the cranial imaging and the presence of borderline psychomotor retardation. A biallelic missense variant, c.656T > C p.(Leu219Ser), was identified in the SC5D gene.Conclusions: Lathosterolosis is a rare cholesterol metabolism disorder and can be presented with a wide range of clinical features by newly reported cases. Lathosterolosis should be considered in cases with cataracts, delayed neuromotor developmental milestones and high levels of liver
Keywords: microcephaly; lathosterol; elevated transaminases; cholesterol metabolism